Once Upon a Christmas Dreary in the Lab of Shakhashiri - Shakhashiri, Bassam Z. (1975)
One of many in a series of annual Christmas lectures given by Bassam Z. Shakhashiri, a Lebanese chemistry educator who spent most of his career at the University of Wisconsin-Madison. The 1975 lecture opens with an introduction from John Weaver, President of the University of Wisconsin system. The experiments demonstrate the properties of gases and liquids, chemical equilibrium, exothermic reactions, chemiluminescence, and the properties of polymers. Also featured are Bucky the Badger, the UW mascot, UW professors Bill Weber and Vince Genna, and retired Chemistry professor Odell Alvestor Taliaferro (Tally). This video was taken from a DVD, which itself was made from an unknown magnetic tape. Any distortions in the image and sound of the video are inherent in the DVD itself.
Keywords: Weaver, John C. (John Carrier), 1915-; Science--Study and teaching; Lectures; Chemistry--Experiments; University of Wisconsin--Madison; Christmas; Liquid nitrogen; Polymers